Instrumentation for Reliably Determining Porous Silicon Photoluminescence Responses to Gaseous Analyte Vapors. Issue 12 (December 2016) - Reynard, Justin M.; Van Gorder, Nathan S.; Richardson, Caley A.; Eriacho, Richie D.; Bright, Frank V.
We report new instrumentation for rapidly and reliably measuring the temperature-dependent photoluminescence response from porous silicon as a function of analyte vapor concentration. The new system maintains the porous silicon under inert conditions and it allows on-the-fly steady-state and time-resolved photoluminescence intensity and hyper-spectral measurements between 293 K and 450 K. The new system yields reliable data at least 100-fold faster in comparison to previous instrument platforms.